Profitabilitas pada Harga Saham Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2018- 2022 - Tartila Tiyasya Putri; Lidya Martha (Universitas 45 Surabaya, 2025)
This study aims to examine the effect of profitability on Stock Prices in companies listed on the Indonesia Stock Exchange. The research population of companies on the Indonesia Stock Exchange in 2018-2022. The sample was selected using a purposive sampling method and a total of 45 companies were obtained. The type of data used is quantitative data and the data source is secondary data obtained from the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The research data was analyzed using the panel data regression method, namely a combination of data from the time series and cross sections through Eviews 12 data processing. The cause of changes in share prices is wrong the other is influenced by internal factors, namely the profitability ratio. In the profitability ratio there are variables Return On Asset, Return On Equity, Return On Investment, Net Profit Margin, and Gross Profit Margin. The research result Return On Asset had a negative and significant effect on stock prices, Return On Equity, Return On Investment, and Gross Profit Margin had a positive and significant effect on stock prices, Net Profit Margin had a negatif and not significant effect on stock prices.